Wallace Carroll papers - Carroll, Wallace, 1906-
Correspondence, memoranda, reports, and propaganda leaflets comprising subject files with narrative histories and inventories documenting Carroll's duties as deputy director for European operations of the U.S. Office of War Information in Washington, D.C. (1944-1945), and, to a lesser extent, as director of the OWI branch in London, England (1942-1944) and his work for the Psychological Strategy Board, the U.S. Dept. of State, and the U.S. Army (1947-1952).
Includes material on the development and implementation of American psychological warfare operations during World War II and Franco-American relations at that time. Includes an analysis (1943) of German defeatism by anthropologist Ruth Benedict; American propaganda leaflets in French, German, Italian, Dutch, Spanish, Czech, and Polish (with translations); reports on the use of psychological warfare in the Cold War; drafts and research material for an article by Carroll for Life magazine on Germany's failure to exploit anti-Stalinist dissidents during its invasion of the Soviet Union in 1941; a report by William L. Langer on U.S. policy toward the Vichy government and North Africa; and letters written by Harold R. Stark, commander of U.S. naval forces in Europe and liaison to exiled French forces in London.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Journalist and psychological warfare strategist. Full name: John Wallace Carroll.
Collection material chiefly in English. Includes American propaganda leaflets in French, German, Italian, Dutch, Spanish, Czech, and Polish (with translations).
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benedict, Ruth, -- 1887-1948.; Langer, William L. -- 1896-1977.; Stalin, Joseph, -- 1879-1953.; Stark, Harold R. -- 1880-1972 -- Correspondence; Psychological Strategy Board (U.S.); United States. -- Army; United States. -- Department of State; United States. -- Navy; United States. -- Office of War Information; Psychological warfare; Cold War -- Psychological aspects; World War, 1939-1945 -- Campaigns -- Soviet Union; World War, 1939-1945 -- Diplomatic history; World War, 1939-1945 -- Governments in exile; World War, 1939-1945 -- Propaganda; World War, 1939-1945 -- Psychological aspects; World War, 1939-1945 -- Public opinion; World War, 1939-1945 -- Africa, North; World War, 1939-1945 -- England -- London; World War, 1939-1945 -- Europe; World War, 1939-1945 -- France; World War, 1939-1945 -- Germany; World War, 1939-1945 -- Washington (D.C.); France -- Foreign relations -- United States; United States -- Foreign relations -- France; Journalists